PENGARUH UKURAN PERUSAHAAN DAN LIKUIDITAS TERHADAP PROFITABILITAS PADA PT. KALBE FARMA TBK PERIODE 2013-2019 - Eman Singgih (Journal Of Communication Education, 2021)
This study aims to determine the effect of Firm Size and Liquidity on Profitability with the object of research being PT Kalbe Farma Tbk for the period 2013-2019. This research is a research  conducted  from  March  to  June  2021  on  the  Jakarta  Stock  Exchange  using  a quantitative approach. Meanwhile, based on the level of explanation, this research includes associative research. The population in this study is the financial statements of PT. Kalbe Farma Tbk for the period 2013-2019. The sample in this study was taken using purposive sampling. This study examines the size of the company using the log of total assets, liquidity is measured by the current ratio and profitability is measured by return on equity.The analytical method used is simple and multiple linear regression, for hypothesis testing using t test and f test with a significance level of 5%. This calculation is assisted by using the SPSS version 18 application. Based on data analysis, Company Size calculated by the log of total assets has a positive and significant effect on Profitability, Liquidity as measured by Current Ratio has a negative and significant effect on Profitability, and Company Size and Liquidity simultaneously significant effect. for Profitability.Keywords: company size, liquidity and profitability